The Impact of Loneliness and Social Isolation on Public Health - Prasetya, Andika; Nurhayati, Siti; Fajar, Rizki (Generasi Sains Indonesia, 2024)
Loneliness and social isolation have emerged as critical public health issues, particularly in the wake of the COVID-19 pandemic. This cross-sectional study investigates the prevalence of loneliness among adults and its association with various health outcomes, including mental health (depression and anxiety) and physical health (hypertension and cardiovascular disease). Data were collected from 500 participants through validated questionnaires, including the UCLA Loneliness Scale and the PHQ-9 for depression. Results revealed moderate levels of loneliness, with significant positive correlations between loneliness and poorer mental health outcomes (r = 0.52, p < 0.001). Furthermore, loneliness was associated with self-reported physical health issues, including hypertension (r = 0.31, p < 0.01) and cardiovascular disease (r = 0.29, p < 0.01). Multiple regression analysis identified younger age, lower socioeconomic status, and urban living as significant predictors of loneliness. These findings underscore the urgent need for public health interventions targeting at-risk populations, particularly younger adults and those in urban settings. As loneliness is increasingly recognized as a risk factor for adverse health outcomes, comprehensive strategies are necessary to mitigate its prevalence and impact. Future research should explore causal pathways and intervention effectiveness to better address this pressing public health challenge.